Uterine intussusception in a crossbred female dog - case report - Silva, D. F. [UNESP]; Carmo, L. M. [UNESP]; Sousa, A. G. [UNESP]; Marques, N. F. S. [UNESP]; Oba, E. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
The present study describes a rare condition of uterine intussusception in a 4 year old crossbred female dog diagnosed by exploratory celiotomy and anatomopathological analysis. As treatment, a ovariohysterectomy (OH) was performed. This pathology usually requires surgical management because the initial diagnosis can be challenging.
Keywords: dog; intussusceptum; invagination; uterus